GE_GERICHTE P/12853/2015 vom 21. Januar 2020 - GE Cour de justice (2020)
QUALITÉ POUR AGIR ET RECOURIR;LÉSÉ;DÉNONCIATEUR;CLASSEMENT DE LA PROCÉDURE;ABUS DE CONFIANCE;ESCROQUERIE;GESTION DÉLOYALE;DOMMAGE | CPP.115; CPP.382; CPP.303; CPP.319.al1.letb; CP.138; CP.146; CP.158